The social auditor - Vinten, Gerald (1990)
The auditor is essentially a social animal. However, beyond this lies a type of audit called “social audit” which tries to strike a balance between an organization's social and more traditional business objectives. After the polar contrasting views of monetarist Friedman amd Marxism have been outlined, we concentrate on considering social audit in the more common mixed economy. With no statutory or other requirement for external social audit, the onus is on organizations to take their own initiatives. Internal resistance often needs to progress through five distinct phases to reach acceptance. Some organizations appoint consumer advocates, such as Esther Peterson. There is an underlying statutory basis to social audits, but if this is extended we enter the domain of external pressure groups, such as the private independent Social Audit and the statutory National Consumer Council. Finally, the scope and motivation for internalizing social audit is discussed.
Keywords: Business Objective; Pressure Group; External Pressure; Internal Resistance; Distinct Phasis